Designing Islamic calendar android apps based on elderly requirements / Mohd Ikhsan Moksin - Moksin, Mohd Ikhsan (2014)
Aging society in every country cannot be denied as well as the increment in the number, there is particular needs or desire on technology dependant. To establish a cohesive and inclusive intergenerational society and put away technology divide that still might exist, technological products and services must be adapted to the needs and preferences of these citizens. Mobile phone is one of the close technology and promising tools to be desired by elderly. Countless application available in stores but it is difficult to determine which of them elder-friendly type is and which is not. Since all the development is based on the dire needs on major population. This research focusing on the development of the prototype of Islamic Calendar apps. It's a compilation from the requirements gathered from elderly and were used as a baseline of the prototype development. The prototype development adopted two design guideline which is Islamic Design guideline and Elderly Design guideline towards the development. This two guideline is the important value that increase the usability of the prototype developed to meet elderly requirements. The work of research provides a foundation for researchers, designers, and mobile phone application developer to think about the existing needs of the elderly, the developing trends in the field and the opportunities that mobile applications offer to improve the apps used elderly and to support a cohesive and inclusive society.